2016
DOI: 10.1002/ange.201607033
|View full text |Cite
|
Sign up to set email alerts
|

Nitrosylation of Nitric‐Oxide‐Sensing Regulatory Proteins Containing [4Fe‐4S] Clusters Gives Rise to Multiple Iron–Nitrosyl Complexes

Abstract: The reaction of protein-bound iron-sulfur (Fe-S) clusters with nitric oxide (NO) playskey roles in NO-mediated toxicity and signaling. Elucidation of the mechanism of the reaction of NO with DNAregulatory proteins that contain Fe-S clusters has been hampered by alack of information about the nature of the iron-nitrosyl products formed. Herein, we report nuclear resonance vibrational spectroscopy( NRVS) and density functional theory (DFT) calculations that identify NO reaction products in WhiD and NsrR, regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 46 publications
2
15
0
Order By: Relevance
“…In all cases nitrosylation resulted in loss of the 412 nm band and emergence of a new band at 357 nm, as previously reported for wild type ScNsrR8, indicating similarity in the final iron nitrosyl products formed7 (Supplementary Fig. 10a and b).…”
Section: Resultssupporting
confidence: 83%
“…In all cases nitrosylation resulted in loss of the 412 nm band and emergence of a new band at 357 nm, as previously reported for wild type ScNsrR8, indicating similarity in the final iron nitrosyl products formed7 (Supplementary Fig. 10a and b).…”
Section: Resultssupporting
confidence: 83%
“…From the NRVS, there was a smaller component of RRE compared to in the NsrR spectrum, and significantly less DNIC present. This is consistent with EPR studies that showed that DNIC accounted for only ~3% of the total initial cluster iron [41,47].…”
Section: Reaction Of Wbl Protein [4fe-4s] Clusters With No M Tubercusupporting
confidence: 77%
“…This species is predicted to have an NRVS spectrum similar to RBS, but importantly with small or no shifts due to the 32 S/ 34 S isotope substitution. DFT calculations also indicated that Cys persulfide forms of these iron-nitrosyls could be present because their calculated NRVS spectra are not significantly different from the Cys thiolate forms [47].…”
Section: Nitrosylation Of [4fe-4s] Nsrrmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo, many transcriptional regulators respond to the presence of aqueous NO, acidified nitrite or S-nitroso-glutathione; in E. coli these include MetR, IscR, Fur, FNR, SoxR, OxyR, NorR and NsrR. This can lead to a dramatic metabolic reorganization in order to adapt to stress conditions (46,48,99,132,146 Figure 7). This species has invariably been detected, both in vivo These studies revealed a rapid multi-NO (~8 per cluster), multi-phasic reaction that appears to be characteristic of [4Fe-4S] cluster containing regulators.…”
Section: Rsrrmentioning
confidence: 99%